2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590894
|View full text |Cite
|
Sign up to set email alerts
|

Polarity detection in ultrasound current source density imaging

Abstract: Modulating the electric dipole field with ultrasound pulse, ultrasound current source density imaging (UCSDI) can detect current direction and form spatial 3D imaging of dipole changing in one period of treatment. As ultrasound pulse passes through the conductive media, it convolves/correlates with the inner product of the electric field of a dipole and lead field of a pair of detectors, making the shifting frequency of polarity lower than the center frequency of the ultrasound pulse. After acoustoelectric (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As an US beam is pulsed and swept in a conductive medium, a recording electrode detects the high frequency AE interaction signal, which is proportional to the local pressure and current. Feasibility of AEI for mapping current densities has been demonstrated in a variety of preparations, including time-varying dipoles (Olafsson et al, 2008, Wang et al, 2011, Wang et al, 2016, Berthon et al, 2017) and imaging of the cardiac depolarization wave in the live rabbit heart (Olafsson et al, 2009, Qin et al, 2015). The primary goals for this study are to 1) assess the performance (spatial resolution, sensitivity, and accuracy) of AEI for detecting and resolving current densities near a DBS device using stimulation parameters resembling those used clinically, and 2) demonstrate feasibility and benchmark performance of AEI through a human skullcap.…”
Section: Introductionmentioning
confidence: 99%
“…As an US beam is pulsed and swept in a conductive medium, a recording electrode detects the high frequency AE interaction signal, which is proportional to the local pressure and current. Feasibility of AEI for mapping current densities has been demonstrated in a variety of preparations, including time-varying dipoles (Olafsson et al, 2008, Wang et al, 2011, Wang et al, 2016, Berthon et al, 2017) and imaging of the cardiac depolarization wave in the live rabbit heart (Olafsson et al, 2009, Qin et al, 2015). The primary goals for this study are to 1) assess the performance (spatial resolution, sensitivity, and accuracy) of AEI for detecting and resolving current densities near a DBS device using stimulation parameters resembling those used clinically, and 2) demonstrate feasibility and benchmark performance of AEI through a human skullcap.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, conventional methods of cardiac potential conduction mapping suffer from low spatial resolution, low SNR, and long imaging times (He and Wu, 2001 ). The ultrasound current source density imaging (UCSDI) is a very effective method for mapping cardiac potential conduction (Li et al, 2012 ), and it has been demonstrated by various techniques (e.g., time-varying dipoles) (Nguyen et al, 2008 ; Wang et al, 2016b ).…”
Section: Research Progressmentioning
confidence: 99%